2020
DOI: 10.3389/fmed.2020.00113
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucose Metabolism Reprogramming in the Pathogenesis of Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is one of the most lethal cancers, and its rate of occurrence is increasing annually. The diagnoses of CCA patients remain elusive due to the lack of early symptoms and is misdiagnosed as HCC in a considerable percentage of patients. It is crucial to explore the underlying mechanisms of CCA carcinogenesis and development to find out specific biomarkers for early diagnosis of CCA and new promising therapeutic targets. In recent times, the reprogramming of tumor cells metabolism has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…However, no increase in Ldha expression was found. On the other hand, it is known that c-myc is a transcription factor that directly activates the genes of the GLUT1 transporter and glycolytic enzymes, such as HK2, phosprofructokinase-1, and enolase-1 [ 51 ]. Furthermore, c-myc is an activator of Ldha expression [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no increase in Ldha expression was found. On the other hand, it is known that c-myc is a transcription factor that directly activates the genes of the GLUT1 transporter and glycolytic enzymes, such as HK2, phosprofructokinase-1, and enolase-1 [ 51 ]. Furthermore, c-myc is an activator of Ldha expression [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose uptake is significantly enhanced in the cancer cells during EMT, which coincides with increased glycolysis (24,25) and lactate secretion that promote tumor invasion and distant metastasis (26,27). It is also reported that the reprogramming of tumor cell metabolism is a macroscopic change, and the change of ICC from oxidative phosphorylation to glycolysis provides favorable conditions for the proliferation of tumor cells (5)(6)(7).…”
Section: Introductionmentioning
confidence: 95%
“…It is the second most common primary liver tumor, and has poor prognosis (1) due to frequent metastasis and recalcitrance to radiotherapy and chemotherapy (2,3). Although notable improvements have been made with different preclinical available cholangiocarcinoma models (4)(5)(6), such as the fibroblast growth factor receptor 2 inhibitor pemigatinib, the first approval of a molecularly targeted treatment in patients with advanced cholangiocarcinoma by US Food and Drug Administration, the prognosis of this disease remains unsatisfactory (7). Therefore, further studies on the molecular mechanism of invasion and metastasis and exploring a novel and effective therapeutic target of ICC are urgently needed (8).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic alteration is a typical hallmark of cancer cells (Chen et al, 2018). The process and the mechanism of cell carcinogenesis were very complex, but the most common and one of the first identified biochemical features of cancer cells was the Warburg effect (Pant et al, 2020). Therefore, we speculated that the inflammatory response may be related to the enhancement of the Warburg effect in normal cells.…”
Section: Introductionmentioning
confidence: 98%